The Effect Of Duration And Working Position On Carpal Tunnel Syndrome Symptoms In Office Workers (A Systematic Review) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Carpal Tunnel Syndrome (CTS) is an upper extremity disorder characterized by pain, numbness, and discomfort caused by compression of the median nerve within the carpal tunnel. CTS commonly occurs due to repetitive activities, excessive force, prolonged mechanical pressure, and non-ergonomic working positions involving the wrist and hand during occupational activities. Office workers are among the occupational groups with high exposure to repetitive computer-related tasks, including typing and mouse usage, which may increase the risk of CTS symptoms. This study aimed to determine the effect of work duration and working position on CTS symptoms among office workers through a systematic literature review approach. This study employed a literature review design using the PRISMA guideline for study selection. Literature searches were conducted through reputable databases, including PubMed, ScienceDirect, and Google Scholar. A total of 11 relevant studies published in national and international journals were included in this review. The analyzed studies primarily used cross-sectional designs involving office employees, administrative workers, typists, designers, and computer users. The findings revealed that six studies reported a significant relationship between prolonged work duration and CTS symptoms, particularly among workers exposed to computer use for more than four hours per day, while several studies found no significant association. Furthermore, all studies examining working position consistently showed that non-ergonomic posture significantly influenced CTS symptoms. Repetitive movements, non-neutral wrist positions, and continuous pressure on the carpal tunnel increased the risk of median nerve compression. In conclusion, prolonged work duration and non-ergonomic working positions contribute significantly to CTS symptoms among office workers. Therefore, ergonomic interventions and proper workstation management are essential to reduce occupational CTS risk.